The Protective Effect of Taurine on Oxidized Fish-Oil-Induced Liver Oxidative Stress and Intestinal Barrier-Function Impairment in Juvenile Ictalurus punctatus - Yong Shi (MDPI AG, 2021)
Dietary lipids provide energy for growth and development and provide fatty acids necessary for normal structure and biological function. However, oxidized lipids cause oxidative stress and intestinal damage. An 8-week feeding trial with fresh fish oil (FFO, control group), oxidized fish oil (OFO), and taurine-supplemented diets (OFOT, OFO + 0.2% of taurine) was conducted to evaluate the protective effect of taurine on oxidized fish-oil-induced liver oxidative stress and intestine impairment in juvenile Ictaluruspunctatus. The results showed that (1) Growth performance was significantly lower in fish fed OFO than in those fed other diets, whereas the opposite occurred in the hepatosomatic index. (2) OFO-feeding significantly increased lipid deposition compared with the FFO group. The addition of taurine ameliorated the OFO-induced increase in lipid vacuolization in the liver, significantly upregulated lpl mRNA expression, and downregulated fas and srebp1 mRNA expression. (3) OFO-feeding significantly reduced oxidative damage of liver. Compared with the OFO group, the OFOT group remarkably upregulated antioxidant enzyme mRNA expression through the Nrf2-Keap1 signaling pathway based on the transcriptional expression. (4) OFO diets induced intestinal physical and immune barrier damage. Compared with the OFO group, OFOT diets remarkably downregulated il-1β, il-6, tnf-α, and il-8 mRNA expression and upregulated tgf-β mRNA expression through the NF-κB signaling pathway. Besides, the addition of taurine to OFO diets significantly upregulated zo-2 and zo-1 mRNA expression, and downregulated claudin-15 and claudin-12 mRNA expression. In conclusion, oxidized-fish-oil diets can cause negative physiological health effects in Ictaluruspunctatus, while adding taurine can increase growth and antioxidant ability, reduce lipid deposition, and improve intestinal health.